Work Stress and Motivation in Determining Student Achievement at Widyatama University - Maharani Ayudhia Cindy,; Ratna Komala Putri, (Technium Social Sciences Journal, 2021)
The purpose of this study was to determine the effect of work stress and motivation in determining student achievement at Widyatama University. The respondents of this study were 130 students who were active in the organization (Student Affairs Organization). This study uses path analysis techniques to answer the research hypothesis, and the research data is obtained through distributing questionnaires to students who are active in organizations. The results of the hypothesis found that simultaneously (Fcount 39,111 > Ftable 3.09) and partially (tcount 3,830 > ttable 1,98; tcount 5,358 > ttable 1,98), it means that the two variables, namely work stress and motivation have a significant effect on student achievement. who are active in organizations. Thus, H1 is accepted and shows that job stress and motivation have a significant effect on the achievement of active student organizations.